Understanding the roles and experiences of key stakeholders involved in the design of the novel imagine social outcomes-based contract in South Africa - Moodley, Gillian Pryadarshini (My University, 2024)
The Imagine Social Outcomes-Based Contract (SOBC) is an innovative health financing mechanism in South Africa applied to sexual and reproductive health outcomes of adolescent girls and young women. The Imagine SOBC is led by the South African Medical Research Council (SAMRC) and supported by other stakeholders. Its uniqueness stems from the role played by the SAMRC, as an intermediary on behalf of the South African government. Eleven semi-structured interviews were held with stakeholders who played intermediary, technical advisor, and implementation service provider roles during the Imagine SOBC design phase. Interviews were transcribed and analysed using the six steps of thematic analysis. The thematic findings of this study are the dynamics of working together, politics and processes, challenges and looking to the future. Despite internal collaboration and alignment among interviewees, the biggest challenge during the design phase of the Imagine SOBC was obtaining approvals from the government departments due to complex approval processes in the public sector. The lessons generated are important as the SAMRC intends to replicate the outcomes-based contract model for other disease priorities. These findings are valuable for policymakers and future outcomes-based contract practitioners who are considering a transaction of this nature and its application to public health. The findings will also assist in the development of a guiding practice note for policymakers and government officials who grant approvals.
A research report submitted in partial fulfilment of the requirement for the degree of Masters of Public Health to the Faculty of Health Sciences, University of the Witwatersrand, School of Public Health, Johannesburg, 2023
Keywords: Medical stakeholders; South African Medical Research Council (SAMRC); SDG-16: Peace, justice and strong institutions; SDG-17: Partnerships for the goals